Penguatan Peran Keluarga dan Kader Posyandu dalam Pencegahan Stunting pada Ibu Hamil melalui Edukasi Gizi di Desa Semen - Hidayah, Nurul; Marwan, Marwan; Martojo, Bambang Riadi Eka (Jaanur Elbarik Indonesia, 2025)
This community service activity aims to provide understanding and education on stunting prevention efforts, starting during pregnancy, by strengthening the role of families and Posyandu (Integrated Service Post) cadres. This community service activity utilizes a nutrition education intervention design with a participatory approach. The target group is 35 pregnant women, 35 accompanying family members (fathers or grandmothers), and 35 Posyandu cadres in Semen village in 2025. Results indicate that nutrition education has proven effective in improving family knowledge, attitudes, and support for stunting prevention. The success of the intervention is influenced by the active involvement of families, especially fathers, as well as strengthening the capacity of Posyandu cadres as agents of change at the community level. Conclusion: Family-based nutrition education and Posyandu cadres are effective in strengthening stunting prevention efforts in pregnant women. This program is recommended for sustainable integration into routine Posyandu activities.